2013
DOI: 10.1002/pmic.201200425
|View full text |Cite
|
Sign up to set email alerts
|

Rice suspension cultured cells are evaluated as a model system to study salt responsive networks in plants using a combined proteomic and metabolomic profiling approach

Abstract: Salinity is one of the major abiotic stresses affecting plant productivity but surprisingly, a thorough understanding of the salt-responsive networks responsible for sustaining growth and maintaining crop yield remains a significant challenge. Rice suspension culture cells (SCCs), a single cell type, were evaluated as a model system as they provide a ready source of a homogenous cell type and avoid the complications of multicellular tissue types in planta. A combination of growth performance, and transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 64 publications
4
27
0
Order By: Relevance
“…Cell cultures are valuable tools to elucidate the complexity of the mechanisms of transduction of exogenous signals, allowing focusing on the biochemistry and cell physiology underlying the maintenance of homeostasis under stress conditions (Grillo et al, 1996;Takahashi et al, 2004). Although the experimental system used represents a simplification of physiological mechanisms adopted by plants, it has been widely demonstrated that the use of plant cell cultures can boost the comprehension of plant-environment interaction (Costa et al, 2010;Dubrovina et al, 2015;Larosa et al, 1987;Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Cell cultures are valuable tools to elucidate the complexity of the mechanisms of transduction of exogenous signals, allowing focusing on the biochemistry and cell physiology underlying the maintenance of homeostasis under stress conditions (Grillo et al, 1996;Takahashi et al, 2004). Although the experimental system used represents a simplification of physiological mechanisms adopted by plants, it has been widely demonstrated that the use of plant cell cultures can boost the comprehension of plant-environment interaction (Costa et al, 2010;Dubrovina et al, 2015;Larosa et al, 1987;Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant related proteins were also detected in previous proteomic studies. In suspension-cultured rice cells under salt stress, GST and glutaredoxin (GRX) contents were down-regulated; however, no change in TRX levels was observed [ 22 ]. Similarly, putative TPx, TRX M-like, putative GSTF3 and TRX x proteins were found down-regulated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…identified 18 salt stress response proteins [ 21 ]. Recently, an isobaric Tags for Relative and Absolute Quantitation (iTRAQ) approach identified at least 521 proteins that responded to salt stress in suspension-cultured rice cells [ 22 ]. To date, there have been no reports investigating the rice shoot proteome under conditions of salt stress using quantitative proteomic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Higher Na + and Cl − concentrations are harmful for photosynthesis and cause a developmental disturbance of plants that is associated with osmotic imbalance and toxic ionic effects plus other nutritional imbalances, such as those of potassium and calcium, and oxidative stress (Geilfus et al, 2015;Munns & Tester, 2008;Nazar, Iqbal, Masood, Syeed, & Khan, 2011). Metabolic responses to salt stress have been studied in model plants such as Arabidopsis (Kim, Bamba, Harada, Fukusaki, & Kobayashi, 2007;Zhang, Zhang, Du, Chen, & Tang, 2011), in diverse crops such as Oryza sativa and Zea mays (Liu et al, 2013;Richter, Erban, Kopka, & Zörb, 2015;Sanchez, Siahpoosh, Roessner, Udvardi, & Kopka, 2008), and in leguminous plants including V. faba, Cicer arietinum, and Lotus japonicus (Dias et al, 2015;Geilfus et al, 2015;Sanchez, Pieckenstain, Escaray, et al, 2011), demonstrating a complex tissue response to NaCl. Diverse metabolomic traits are associated with enhanced NaCl tolerance (Del-Saz et al, 2016;Richter et al, 2015;Sanchez, Pieckenstain, Escaray, et al, 2011;Widodo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%